Development, Validity, and Practicality of Articulate Storyline–Based Audiovisual Mobile Learning Materials for Tennis Instruction - Septian Raibowo; Joan Siswoyo; Eko Risdianto; Bogy Restu Ilahi; Oddie Barnanda Rizky (CV. Creative Tugu Pena, 2025)
This study aimed to develop and evaluate the validity and practicality of Articulate Storyline–based audiovisual teaching materials integrated into a mobile learning platform for university-level tennis instruction. This Research and Development (R&D) study followed the Analysis, Design, and Development stages of the ADDIE model. Product validity was evaluated by two media experts and two subject-matter experts using Aiken’s V coefficient. Practicality testing involved one tennis-course lecturer and 90 students, comprising 30 students in a small-group trial and 60 students in a large-group trial. Practicality data were analyzed descriptively and expressed as percentages. The media and content evaluations each produced a mean Aiken’s V coefficient of 0.86, indicating that both aspects were highly valid. The overall combined validity coefficient was also 0.86. Student practicality scores increased from 82.5% in the small-group trial to 85.0% in the large-group trial, with an overall mean of 83.8%, categorized as highly practical. The highest-rated indicator was the clarity of the technique-demonstration videos (88.2%), whereas interface navigation received the lowest score (79.4%). The lecturer assessment yielded a practicality score of 90.6%, which was also categorized as highly practical. These findings confirm that the developed teaching materials satisfy the established validity and practicality criteria for use in tennis courses. Articulate Storyline–based audiovisual mobile learning materials are highly valid and practical for supporting university-level tennis instruction. Further studies should evaluate their effectiveness in improving students’ cognitive learning outcomes and basic tennis skills